ALKYL-MODIFIED VINYL ALCOHOL POLYMER, AND COMPOSITION, THICKENER, COATING MATERIAL FOR PAPER, COATED PAPER, ADHESIVE AND FILM CONTAINING THE SAME - NII Shinsuke; SAITO Yasutomo; NAKAMAE Masato; TAOKA Yuta (2018)
An object of the invention is to provide a novel alkyl-modified PVA capable of exerting superior thickening properties while maintaining high water solubility, and also capable of having high water resistance in a state being hardened without using an especial crosslinking agent. In addition, another object is to provide a composition, a thickener, a coating material for papers, a coated paper, an adhesive and a film containing the alkyl-modified PVA. Provided is an alkyl-modified vinyl alcohol polymer containing (a) a monomer unit represented by the following general formula (I): wherein, R 1 represents a linear or branched alkyl group having 8 to 29 carbon atoms; and R 2 represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, and has a viscosity average degree of polymerization of no less than 200 and no greater than 5,000, a degree of saponification of no less than 20 mol% and no greater than 99.99 mol%, and a content of the monomer unit (a) of no less than 0.05 mol% and no greater than 5 mol%.